FOLATES AND PERSEA AMERICANA MILL. (AVOCADO) - Pacheco, M. M. Martinez; Gomez, R. Lopez; Garciglia, R. Salgado; Calderon, M. Raya; Muñoz, R. E. Martinez (Emirates Journal of Food and Agriculture, 2011)
In developing countries there has been a rapid increase in the number of cases of metabolic disorders associated to human lifestyle. A rich diet of refined foods, poor in micronutrients has a direct correlation with human metabolic disorders and other diseases. The aim of this study is to reassess the role of indigenous foods, its richness in micronutrients and its re-inclusion in the diet of local man. This cultural factor could minimize the negative impact caused by the lack of micronutrients such as the folates in human health. The Avocado (Persea americana Mill.) fruit is native of Central America and is an ancestral food that bear folates. We review the synthesis of folates pathway in plants, cultural and economic importance of the fruit of avocado as ancestral food of the inhabitants of the land bridge that links both the North and South American sub-continents. The important micronutrients such as folates in relieving some metabolic disorders and syndromes associated with human lifestyle are also reviewed in this study.